An Empirical Inquiry Into Cartel Overcharges and Cartel Fines Including an Assessment of the EU's Guidelines on Cartel Fines and Damages - Justus Haucap; Mehmet Karacuka; Hakan Inke (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Utilizing Connor's International Cartel Database and employing difference-in-differences methodology, we find that market concentration, the number of buyers and cartel duration have significant impacts on cartel overcharges. We also find that the European Commission's 2006 guidelines on the method of setting fines for cartel infringements seems to have decreased cartel overcharges in the EU. In addition, the EU's cartel damages directive of 2014 (2014/104/EU) appear to have increased private damage payments. Overall, we find support that these two changes in EU competition policy have a reversing impact on the otherwise increasing trend of cartel overcharges, as making the infringement more costly at least in the EU.
Keywords: L41; K21; 330; cartel fines; cartel damages; EU guidelines; competition law; antitrust